The potential of cognitive think-aloud protocols for educational action-research. (November 2019) - Cowan, John
This article presents the case for the use of the 'think-aloud protocol' by teachers who engage in action-research as a source of constructive information about their students' cognitive learning processes. This method calls upon learners to talk their thoughts out aloud, during engagement in some learning activity regarding which the researching teachers seek insight to inform them to plan enhancement of the learning and teaching process. The case for 'think-aloud' reporting of particular learning activities is supported by a review of relevant literature. Accounts of diverse experiences in various discipline areas using modified versions of think-aloud protocols in action-researching are presented, with reports of their transformative outcomes. Reasoned reservations regarding the reliability of uncorroborated sources of retrospective data about students' learning are advanced. Refined methodologies are outlined together with general guidelines, for those minded to explore their value in their own contexts.